Use of high-throughput liquid chromatography mass spectrometry to measure association between vitamin D metabolites and body composition and muscle mass: a cross-sectional study. (25th February 2016) - Hassan-Smith, Zaki; Jenkinson, Carl; Taylor, Angela; Morgan, Stuart; Hughes, Beverly; Adams, John; Keevil, Brian; Stewart, Paul; Hewison, Martin
Abstract: Background: Sarcopenia contributes to functional decline and metabolic dysfunction in elderly people, and there is no accepted pharmacological treatment. Vitamin D deficiency is common, and can affect tissues such as muscle. Existing assays focus on one metabolite, 25-hydroxyvitamin D3 (25(OH)D3). We aimed to perform high-throughput analysis of vitamin D metabolites with novel liquid chromatography tandem mass spectrometry (LC-MS/MS) techniques to evaluate the association between vitamin D metabolites and body composition and muscle function. Methods: This cross-sectional observational study was carried out at the National Institute for Health Research-Wellcome Trust Clinical Research Facility. Participants were healthy non-obese volunteers. We performed body composition analysis (DEXA), assessed grip strength, measured serum metabolites of vitamin D (LC-MS/MS) and glucocorticoids in 24 h urine collection (gas chromatography mass spectography), and determined gene expression in vastus lateralis biopsy samples. Non-parametric testing was completed. Research ethics committee approval was obtained. Findings: 116 volunteers took part in the study (79 women, 37 men; age range 20–74 years). Body fat correlated negatively with 25(OH)D3 and 3-epi-25(OH)D3 (Pearson r =−0·20 [p=0·04] and −0·21 [p=0·03], respectively). Total lean mass correlated positively with 3-epi-25(OH)D3 ( r =0·24, p=0·02) but not with 25(OH)D3. Grip strength correlated positively with 3-epi-25(OH)D3 ( r =0·22, p=0·04) but not with 25(OH)D3. In women, the tetrahydrocortisol plus 5α-tetrahydrocortisol to tetrahydrocortisone ratio (an 11β-HSD1 activity marker) in urine correlated negatively with serum 25(OH)D3 ( r =−0·31, p=0·02) and 24, 25(OH)2D3 ( r =−0·26, p=0·04). Conversely urinary cortisol to cortisone ratio (an 11β-HSD2 activity marker) correlated positively with 25(OH)D3 ( r =0·28, p=0·04), 24, 25(OH)2D3 ( r =0·29, p=0·03), and 25(OH)D2 ( r =0·35, p=0·04). Serum 25(OH)D3 and 3-epi-25(OH)D3 correlated positively with genes with anabolic functions in muscle including myogenin, myosin chain components, and insulin and IGF1 receptors. Interpretation: Using a novel high-throughput approach, we found that vitamin D metabolites, including epimers, correlated with reduced fat mass and increased lean mass and grip strength. Data were also consistent with effects on 11β-HSD function, which we have previously shown to be important in determining muscle mass and strength. Large scale supplementation trials are required to examine the therapeutic potential in sarcopenia and obesity. Funding: The clinical study was funded by a European Research Council Advanced Grant awarded to PS. Vitamin D analyses and method development were funded by a National Institues of Health P50 grant awarded to MH and JA (AR063020-01 NIH/NIAMS).